PENGARUH PENGENDALIAN INTERN TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. BROTHER SILVER - Lasso, Ananta Budi; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is aimed to test whether internal controls has an influence to the performance of production employees of PT. Brother Silver Products Indonesia Sidoarjo. The sampling technique has been carried out by using proportionate stratified random sampling. The data used is the primary data which has been obtained by issuing questionnaires which are filled in by the production employees of PT. Brother Silver Products Indonesia Sidoarjo as the human resources (HR). The result of the test shows that the influence of internal control has significant and positive influenced to the performance of the employees, control activities has significant and positive influenced to the performance of the employees and monitoring has significant and positive influenced to the performance of the employees. This condition indicates that this research model can be continued in the following analysis. These results are confirmed by the acquisition of the correlation coefficient of 82.5% which shows that simultaneously the correlation or relationship among variables to the performance of the production employees of PT. Brother Silver Products Indonesia Sidoarjo as human resources is firm.Keywords: Control environment, control activities, monitoring and the performance of the employees.